2006
DOI: 10.1111/j.1750-3841.2006.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Acceptability and Stability of Probiotic Microorganisms and Vitamin C in Fermented Acerola (Malpighia emarginata DC.) Ice Cream

Abstract: Six fermented acerola ice creams were produced, containing different starter cultures (Bifidobacterium longum, Bi.lactis, and traditional yogurt starter culture—Streptococcus thermophilus and Lactobacillus delbrueckii spp. bulgaricus) and final pH (5 and 4.5). The ice creams were evaluated for probiotic culture viability, vitamin C stability, and sensory acceptance. Mix fermentations were stopped when pH 5.0 and 5.5 were attained. However, after the addition of acerola pulp the determined pH were 4.5 and 5, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
2
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 18 publications
5
28
2
5
Order By: Relevance
“…The authors suggested that adding highly acidic fruit to ice cream might be useful in masking the sour taste resulting from the metabolism of probiotic cultures. However, these results should not be generalized, as opposite findings were reported by Fávaro-Trindade et al (2006) for probiotic ice cream with acerola fruit.…”
Section: Sensory Characteristics Of Probiotic Ice Creamcontrasting
confidence: 66%
See 3 more Smart Citations
“…The authors suggested that adding highly acidic fruit to ice cream might be useful in masking the sour taste resulting from the metabolism of probiotic cultures. However, these results should not be generalized, as opposite findings were reported by Fávaro-Trindade et al (2006) for probiotic ice cream with acerola fruit.…”
Section: Sensory Characteristics Of Probiotic Ice Creamcontrasting
confidence: 66%
“…Davidson et al (2000) reported that, in general, ice creams fermented with probiotic cultures presented weaker aroma and taste (poor sensory performance) compared to those fermented with traditional yogurt starters. Thus, the production of probiotic ice creams with high sensory acceptance is a difficult task (Aryana and Summers 2006;Fávaro-Trindade et al 2006;Hekmat and McMahon 1992). However, it is possible to develop probiotic ice cream with good sensorial quality (Christiansen et al 1996;Vardar and Öksüz 2007).…”
Section: Sensory Characteristics Of Probiotic Ice Creammentioning
confidence: 96%
See 2 more Smart Citations
“…Por outro lado, a utilização de probióticos em produtos congelados funcionais é bastante promissora, pois o fato de serem conservados a baixas temperaturas os torna mais propensos a manter a dose viável destes microrganismos por toda sua vida de prateleira (DUTHIE et al, 1982;HEENAN et al, 2004, FAVARO-TRINDADE et al 2006FAVARO-TRINDADE et al 2007). …”
Section: Introductionunclassified